2008
DOI: 10.1111/j.1472-4642.2008.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the widespread marine invader Microcosmus squamiger (Ascidiacea) reveals high genetic diversity of introduced populations and non‐independent colonizations

Abstract: The spread of non‐indigenous species into new marine habitats represents an increasing threat to global diversity. Genetic techniques provide basic understanding of the invasion processes. The ascidian Microcosmus squamiger is considered to be native to Australia, having been spread worldwide via transoceanic vessels. It has successfully invaded artificial and natural habitats where it has become a pest. We studied phylogeography and genetic structure of 12 M. squamiger populations, including samples from its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 65 publications
6
62
1
Order By: Relevance
“…Given the hermaphrodite mode of reproduction in M. leidyi, our findings underline the importance of reproductive strategies for invasion success, despite losses in genetic diversity (Roman & Darling 2007). Finally, our study contributes to the growing evidence that not all invasions need to be accompanied by losses of genetic diversity (Rius et al 2008, Brown & Stepien 2009) and successful invasions can vary broadly in their degree of genetic diversity (Darling et al 2008). …”
Section: Southern Invasion and Spread Into The Mediterranean Seamentioning
confidence: 52%
“…Given the hermaphrodite mode of reproduction in M. leidyi, our findings underline the importance of reproductive strategies for invasion success, despite losses in genetic diversity (Roman & Darling 2007). Finally, our study contributes to the growing evidence that not all invasions need to be accompanied by losses of genetic diversity (Rius et al 2008, Brown & Stepien 2009) and successful invasions can vary broadly in their degree of genetic diversity (Darling et al 2008). …”
Section: Southern Invasion and Spread Into The Mediterranean Seamentioning
confidence: 52%
“…The more subtle deviations found in samples of C. nucula and M. squamiger may represent secondary contact between divergent lineages (Duran and Rützler, 2006;Rius et al, 2008), whereas that shown by E. superba probably reflects the exceptional abundance and mixing of swarms of this species (GoodallCopestake et al, 2010). An explanation for the slight deviation of the P. zostericola sample is not obvious on the basis of the corresponding publication (Haig et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Information on genetic structure of introduced populations has revealed important features of invasion events, such as timing and source or sources of introductions, pathways and vectors, as well as the importance of propagule pressure during the introduction process (e.g. Roman & Palumbi 2004, Lockwood et al 2005, Provan et al 2005, Rius et al 2008, Dupont et al 2010. The long-held idea that introduced populations have low genetic diversity due to founder effects and bottlenecks has been challenged by the finding of unexpectedly high levels of genetic diversity in introduced populations, which is attributable to recurrent introductions from diverse sources (Lambrinos 2004, Roman & Darling 2007, Dlugosch & Parker 2008, Wilson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ascidians, which are recognized as being major invaders around the world (Dupont et al 2007, Lambert 2007, Rius et al 2008, Stefaniak et al 2009, Zhan et al 2010, have an important effect on natural ecosystems and economic implications (Lambert 2007). Perophora japonica Oka, 1927 is one of several introduced colonial ascidians found in European seas (Nishikawa et al 2000, Arenas et al 2006, Gittenberger 2007.…”
Section: Introductionmentioning
confidence: 99%